Removal and Biodegradation of Phenanthrene, Fluoranthene and Pyrene by the Marine Algae Rhodomonas baltica Enriched from North Atlantic Coasts - Arias, Andres Hugo; Annisa, Souissi; Glippa, Olivier; Roussin, Marion; Dumoulin, David; Net, Sopheak; Oudanne, Baghdad; Souissi, Sami (Bulletin of Environmental Contamination and Toxicology)
This study is focused on the removal, accumulationand degradation of three environmental ubiquitouspolycyclic aromatic hydrocarbons (PAHs), phenanthrene(PHE), luoranthene (FLA) and pyrene (PYR), by themarine alga Rhodomonas baltica enriched from the EnglishChannel. After separation, puriication and culture inseveral phases, R. baltica was exposed to PAH concentrationsthat are frequently encountered in the ield in severalanthropized environments. The results showed thatR. baltica can grow under PAH stress, eiciently removeup to 70% of these compounds from the medium by 216 hof culture and selectively bioaccumulate PAHs by theirhydrophobicity. Between PHE, FLA and PYR, phenanthrenewas the compound with higher degradation ratesthroughout incubation. The equilibrium partitioning theoreticalapproach showed that physico-chemical partitioning,rather than active bioconcentration, was the major factorgoverning the bioaccumulation, outlying a potential applicationin decontamination processes for this species. Fil: Arias, Andres Hugo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina. Universidad Nacional del Sur; Argentina Fil: Annisa, Souissi. Universitè de Lille; Francia Fil: Glippa, Olivier. Universitè de Lille; Francia Fil: Roussin, Marion. Universitè de Lille; Francia Fil: Dumoulin, David. Universitè de Lille 1; Francia Fil: Net, Sopheak. Universitè de Lille 1; Francia Fil: Oudanne, Baghdad. Universitè de Lille 1; Francia Fil: Souissi, Sami. Universitè de Lille; Francia